Approximations to the truth: Comparing survey and microsimulation approaches to measuring income for social indicators - Francesco Figari; Maria Iacovou; Alexandra Skew; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2010)
This paper evaluates income distributions in four European countries (Austria, Italy, Spain and Hungary) using two complementary approaches: a standard approach based on reported incomes in survey data, and a microsimulation approach, where taxes and benefits are simulated. Given that benefit receipts tend to be under-reported in survey data, and over-estimated in microsimulation procedures, we may expect the two approaches to generate slightly different results. In fact, we find reasonably consistent results. To the extent that the results differ, we explore why these differences occur, and suggest directions for future research, where each approach may inform improvements in the other.
Keywords: C81; D31; I32; 330; income; microsimulation; poverty; inequality; Europe; Einkommensverteilung; Soziale Ungleichheit; Vergleich; Befragung; Simulation; Österreich; Ungarn; Spanien; Italien